2017
DOI: 10.1097/mpa.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Novel Subtype-Specific Protein Biomarkers in Pancreatic Ductal Adenocarcinoma

Abstract: The study reports the identification and validation of novel PDAC biomarkers relevant for the development of patient stratification tools. In addition, cadherin-17 and galectin-4 may serve as targets for bispecific antibodies as novel therapeutics in PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…As a result, the implications of tumour cellularity on transcriptomic analysis remain a priority area of research. However, several studies have demonstrated that epithelial cell lines of PDAC recapitulate published transcriptomic subtypes, including transcripts native to pancreatic exocrine and endocrine cells defining an aberrantly differentiated endocrine exocrine subtype (ADEX).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the implications of tumour cellularity on transcriptomic analysis remain a priority area of research. However, several studies have demonstrated that epithelial cell lines of PDAC recapitulate published transcriptomic subtypes, including transcripts native to pancreatic exocrine and endocrine cells defining an aberrantly differentiated endocrine exocrine subtype (ADEX).…”
Section: Discussionmentioning
confidence: 99%
“…Collisson and colleagues have classified pancreatic cancer into three molecular subtypes, that is, classical, exocrine-like and quasimesenchymal, with each subtype presenting different response rates to therapy and survival [19]. Notably, by a recent proteomics approach, galectin 4 was identified as a biomarker for the exocrine-like subtype, characterized by resistance to tyrosine kinase inhibitors and paclitaxel [20]. This information has high clinical relevance as it indicates that galectin 4 expression may be used to predict the response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In primary colorectal cancers and intestinal metaplasia of the stomach, CDX2 and CDH17 expression are highly correlated in a positive way as CDX2 promotes CDH17 expression [26]. CDH17 is highly expressed in hepatocellular carcinoma [32][33][34], gastric cancer [35,36], pancreatic cancer [37,38]-and particularly in the exocrine-like subtype of pancreatic ductal adenocarcinoma [39], esophagus carcinoma, neuroendocrine tumors [40,41] and colorectal cancer [26,38,42,43]-with 96% of tumor samples showing expression of this molecule [38] ( Table 1). Different studies have described a clear association of high expression of CDH17 with either lung [42] or liver metastasis in human colon cancer [44], in which it correlates with poor prognosis [45].…”
Section: Accepted Manuscriptmentioning
confidence: 99%